STATE PRESENCE AND DIGITAL SERVICES PLATFORM - Linares Torres, Freddy (2023)
This article consists of a qualitative analysis of different sources on the digitalisation of the Peruvian state and its services in the new digital society. The expansion of the internet has accelerated along with the advance of recent technological disruptions with a relevant impact on the interests and capabilities of the population. The essence of technology lies in optimisation, so its integration through the digitisation of society was logical as its efficiency increased. This process impacts relationships, social dynamics, as well as the horizons of state action. Taking advantage of and integrating these resources is necessary to boost the development of countries like Peru, but it must be done strategically. The first step is the digitalisation process of public services, which must include giving sufficient relevance to coordinating the design and implementation of regulations and new digital infrastructure. But in addition to creating new digital channels, seeking the correct articulation between digital services and resources is necessary. In this way, the State will be consolidated as a unified platform of services and become an efficient digital entity at the service of digital users. Finally, guaranteeing the integration of national cyber defence will be vital to ensuring the stability and protection of the new digital platform and its users. This transformation will ensure the successful adaptation of the public apparatus and its services to the trends and disruptive waves that will continue to develop in the near future.